On the Typical Spectral Shape of an Economic Variable - Daniel Levy; Hashem Dezhbakhsh (Bar-Ilan University, Department of Economics, 2002)
In a classic article, Granger (1966) asserted that most economic time series measured in level have spectra that exhibit a smooth declining shape with considerable power at very low frequencies. There has been no systematic attempt to examine Granger,s assertion with international data. We estimate output level spectra for 58 countries, divided into developed, high-income developing, and low-income developing groups. We find the shapes of the estimated spectra to be strikingly similar to Granger"s typical shape, particularly for the developed countries.
Keywords: E32; O40; O57; 330; Spectral Analysis; Spectral Shape; Output Level; OECD; Developing Countries